Propyl Gallate Exerts an Antimigration Effect on Temozolomide-Treated Malignant Glioma Cells through Inhibition of ROS and the NF-κB Pathway - Jen-Tsung Yang; I-Neng Lee; Fung-Jou Lu; Chiu-Yen Chung; Ming-Hsueh Lee; Yu-Ching Cheng; Kuo-Tai Chen; Ching-Hsein Chen (Journal of Immunology Research)
In this study, we demonstrated that temozolomide (TMZ) and propyl gallate (PG) combination enhanced the inhibition of migration in human U87MG glioma cells. PG inhibited the TMZ-induced reactive oxygen species (ROS) generation. The mitochondrial complex III and NADPH oxidase are two critical sites that can be considered to regulate antimigration in TMZ-treated U87MG cells. PG can enhance the antimigration effect of TMZ through suppression of metalloproteinase-2 and metalloproteinase-9 activities, ROS generation, and the NF-κB pathway and possibly provide a novel prospective strategy for treating malignant glioma.